2021
DOI: 10.1093/europace/euaa336
|View full text |Cite
|
Sign up to set email alerts
|

Sinus rhythm voltage fingerprinting in patients with mitral valve disease using a high-density epicardial mapping approach

Abstract: Aims Unipolar voltage (UV) mapping is increasingly used for guiding ablative therapy of atrial fibrillation (AF) as unipolar electrograms (U-EGMs) are independent of electrode orientation and atrial wavefront direction. This study was aimed at constructing individual, high-resolution sinus rhythm (SR) UV fingerprints to identify low-voltage areas and study the effect of AF episodes in patients with mitral valve disease (MVD). Methods and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…In the present study, we did not correlate low-voltage areas with CV, as it remains very challenging to identify a correct threshold to define low-voltage areas. Additionally, prior high-resolution epicardial mapping studies demonstrated no clear relationship between CV and low voltage areas [14,39]. In our study population, in general we have found lower voltages at BB in patients with AF compared to patients without AF.…”
Section: Low Voltages and Atrial Fibrillationcontrasting
confidence: 49%
“…In the present study, we did not correlate low-voltage areas with CV, as it remains very challenging to identify a correct threshold to define low-voltage areas. Additionally, prior high-resolution epicardial mapping studies demonstrated no clear relationship between CV and low voltage areas [14,39]. In our study population, in general we have found lower voltages at BB in patients with AF compared to patients without AF.…”
Section: Low Voltages and Atrial Fibrillationcontrasting
confidence: 49%
“…Van Schie et al have demonstrated that unipolar voltage is lower in areas of slowed conduction or CB, or areas containing fractionated potentials, which might indicate areas of arrhythmogenic tissue. 70 In this study, unipolar LVAs were found in all 67 patients with MVD with and without a history of paroxysmal AF, although lower voltages and more LVAs were found at BB in paroxysmal AF patients. There were no predilection sites for low voltages to occur.…”
Section: Unipolar Voltage Mappingmentioning
confidence: 48%
“…In the late 1990s, Konings et al described a classification of U-EGMs based on the number of negative deflections, which is easy to measure, especially during SR. 75 Van Schie et al have demonstrated that MVD patients with paroxysmal AF had more unipolar fractionated potentials at the PV area compared to those without a history of AF. 70 However, fractionation can also be a consequence of variation in the anatomy of the atrial wall and therefore functional anisotropy. U-EGM and Bi-EGM fractionation has also been linked to asynchronous activation of the endo-and epicardium, which may be a significant mechanism for the persistence of AF.…”
Section: Use Of Electrogram Morphology and Fractionationmentioning
confidence: 99%
“… 26 Although unipolar electrograms are not affected by directional sensitivity, substrate assessment by solely unipolar voltage is also limited. 36 We found that even in omnipolar LVAs there are still high unipolar voltages and a large variety of CVs. The logarithmic relationship between RA CV and bipolar voltage found by Itoh et al 30 also shows that for a relatively narrow interval of bipolar voltages a broad spectrum of CVs can be found.…”
Section: Discussionmentioning
confidence: 67%